2018
DOI: 10.3390/pharmacy6030085
|View full text |Cite
|
Sign up to set email alerts
|

Medication-Related Burden among Patients with Chronic Disease Conditions: Perspectives of Patients Attending Non-Communicable Disease Clinics in a Primary Healthcare Setting in Qatar

Abstract: This study aimed to assess perceived medication-related burden among patients with multiple non-communicable diseases (NCDs) and to investigate the association between perceived burden and adherence to medication therapy. Using a cross-sectional study in three primary care clinics in Qatar, medication-related burden was measured using the Living with Medicines Questionnaire (LMQ) among adults with diabetes, with or without other comorbidities. Adherence was measured using the Adherence to Refills and Medicatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
39
10

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(61 citation statements)
references
References 31 publications
10
39
10
Order By: Relevance
“…However, these comparisons should be considered with caution due to the differences in the methodologies and health systems. Our present findings revealed that the vast majority of the study population reported experiencing minimal (35.4%) to moderate (62.0%) degrees of MRB, which is different from that reported in Qatar, minimal (66.8%) to moderate (24.1%) and in England, minimal (33.1%) to moderate (53.6%) degrees of burden, respectively (Zidan et al, 2018;Krska et al, 2019). This may be due to the differences among the study populations, both studies assessed MRB among patients aged ≥ 18 years.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…However, these comparisons should be considered with caution due to the differences in the methodologies and health systems. Our present findings revealed that the vast majority of the study population reported experiencing minimal (35.4%) to moderate (62.0%) degrees of MRB, which is different from that reported in Qatar, minimal (66.8%) to moderate (24.1%) and in England, minimal (33.1%) to moderate (53.6%) degrees of burden, respectively (Zidan et al, 2018;Krska et al, 2019). This may be due to the differences among the study populations, both studies assessed MRB among patients aged ≥ 18 years.…”
Section: Discussioncontrasting
confidence: 99%
“…than those aged 65-74 years old. This finding is in contrast to the Qatari and English studies, which reported that LMQ overall scores were not strongly related to age (Katusiime et al, 2018;Zidan et al, 2018), and another English study that showed a significantly lower mean LMQ overall scores among elderly patients (≥ 65 years) compared with adult patients (18-64 years) and a nonsignificant difference among the older patient groups, 65-79 years vs. ≥ 80 years (Krska et al, 2018). The possible explanation for the high burden among respondents aged ≥75 years may be due to their significantly higher scores in two domains related to communication/relationships with healthcare professionals about medicines and perceived effectiveness of medicines, which revealed their poorer quality relationships with healthcare professionals and less satisfaction with medication effectiveness.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations